Picturing truth and reconciliation - Liebmann Marian (Temida)
This is an account of the workshop run at the conference Truth and reconciliation in the former Yugoslavia: Where are we now and where to go? Even in such a short workshop, it seemed that it was possible to share difficult areas of the past, and move on to looking at hopes for the future. The use of art materials seemed to facilitate the expression of aspects difficult to put into words. There seems to be potential for extending this method. Yet it is not without its dangers, if used with a vulnerable group of people, or in an insecure situation, or in an insensitive way. It could open doors which are difficult to shut again. The ability of art to bring up memories and emotions is both its strength and its risk.